Comparison of Selected Agro-Based Filter Media for Stormwater Quality Improvement - Abdul Taha, Nazaruddin; Awang Ali, Awang Nasrizal; Awang Aziz, Ani Aryanie; Bolong, Nurmin; Abdul Taha, Nazaruddin (International Journal of Integrated Engineering, 2022)
Polluted stormwater has become a severe problem in the environment as the runoff collecting various contaminants before discharged into water bodies, degrading the water quality and risking aquatic life. This study aims to evaluate selected agro-based filter media to treat stormwater through environmental laboratory works. These include kernel shell, coconut husk, coconut shell, durian shell, sugarcane bagasse, and pineapple leaves. The stormwater samples used were collected from a pond in Universiti Malaysia Sabah, whereas the filter column is configured through a combination of 80% of agro-based media and 20% of aggregate. Filter performance is evaluated for turbidity, pH, dissolved oxygen, biochemical oxygen demand, and ammoniacal nitrogen. Overall, the findings show the potential in utilizing agro-based media, particularly the shell-based media of CS300, KS300, and DS200. Further investigations are recommended to further study the application of agro-based media in improving the quality of stormwater